Povysenie kvalifikacii specialistov po fiziceskoj kul'ture i sportu c SPbGUFKe im. P. F. Lesgafta - Losin, B. E. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The first faculty of improvement of professional skill in system of sports high schools of the country has been formed in 1968 in the state twice decorated with an order P.F. Lesshaft's institute of physical culture. The new faculty has acted as one of the first in the country in a role of propagation of modern scientific ideas in the field of physical culture and sports. Today educational process is conducted by known scientists and teachers of university, and also the best trainers of Russia. Among them more than 40 person have scientific degrees of doctors of sciences and ranks of professors, more than 15 person - ranks of the honoured coaches. It allows to support educational process at a high scientific-methodical level.